PENGARUH DIVIDEND POLICY TERHADAP SHARE PRICE VOLATILITY PERUSAHAAN CONSUMER NON-CYCLICALS YANG TERDAFTAR DI BEI - Naufal Ramadhani; Susy Muchtar (STKIP Persada Khatulistiwa Sintang, 2023)
This study aims to examine the effect of dividend policy on share price volatility of companies in the consumer non-cyclicals industry. The samples used in this research are 19 consumer non-cyclicals companies that have been listed on Indonesia Stock Exchange for 5 years (2017-2021). The type of data contained in this research is secondary data. The sampling technique in this study used purposive sampling and the analytical method used regression and panel data. The independent variables in this study consist of dividend payout, dividend yield, dividend per share, leverage, and firm size, while the dependent variable is share price volatility. The results of panel data regression show that dividend payout, dividend yield, and firm size have no significant positive effect on share price volatility, dividend per share has no significant negative effect on share price volatility, and leverage has a significant negative effect on share price volatility. This research is important so that companies and investors can find out what factors can affect the share price volatility of a company’s shares in order to get the maximum return in accordance with their respective risk profiles